2020
DOI: 10.1089/mdr.2019.0290
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Duplication Within pmrB Gene Contribute to High-Level Colistin Resistance in Avian Pathogenic Escherichia coli

Abstract: Beyond the emergence of plasmid-encoded mechanisms, mutation within the pmrAB genes remains one of the primary colistin resistance mechanisms in Escherichia coli. However, the mechanisms of high-level colistin resistance (HLCR) have not been elucidated. In this study, we evaluated the HLCR mechanisms in five colistinsusceptible Avian pathogenic Escherichia coli (APEC) isolates after colistin exposure. Three PmrB substitutions (G19R, L167P, V88E) and two PmrB sequence duplication (PmrB-sd) mutations (68-77dup a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The colistin-carbapenem resistant isolate identified in this study lacked an mcr -type gene but revealed chromosomal mutations within pmrB , phoP , phoQ and pmrD genes. Some of the detected amino acid variations have previously been reported from colistin resistant E. coli isolates including PmrB D283G [ 25 ], PmrB G19R [ 26 ], PmrB H2R/ A360V, PhoP I44L, PhoQ L467M and PmrD N11D/M20K/A27T /K82Q/V83S [ 27 ]. More importantly we found that two CRE isolates belonging to ST167 and ST648 co-harbored 16S rRNA methyltransferase RmtB/RmtC and NDM-type carbapenemases.…”
Section: Discussionmentioning
confidence: 99%
“…The colistin-carbapenem resistant isolate identified in this study lacked an mcr -type gene but revealed chromosomal mutations within pmrB , phoP , phoQ and pmrD genes. Some of the detected amino acid variations have previously been reported from colistin resistant E. coli isolates including PmrB D283G [ 25 ], PmrB G19R [ 26 ], PmrB H2R/ A360V, PhoP I44L, PhoQ L467M and PmrD N11D/M20K/A27T /K82Q/V83S [ 27 ]. More importantly we found that two CRE isolates belonging to ST167 and ST648 co-harbored 16S rRNA methyltransferase RmtB/RmtC and NDM-type carbapenemases.…”
Section: Discussionmentioning
confidence: 99%